Biosynthesis of nanoparticles and silver nanoparticles - Abd. Aziz, Azila (2015)
In this century, the development of nanotechnology is projected to be the establishment of a technological evolutionary of this modern era. Recently, nanotechnology is one of the most active subjects of substantial research in modern material sciences and hence metal nanoparticles have a great scientific interest because of their unique optoelectronic and physicochemical properties with applications in diverse areas such as electronics, catalysis, drug delivery, or sensing. Nanotechnology provides an understanding on fundamental properties of objects at the atomic, molecular, and supramolecular levels. Besides, nanotechnology also leads an alternative technological pathway for the exploration and revolution of biological entities, whereas biology provides role models and biosynthetic constituents to nanotechnology. The findings of this review are important to provide an alternative for the green synthesis of silver nanoparticles. It showed more cost-effective and environmental friendly application as well as easier for large production, with relation to the properties of silver nanoparticles as antimicrobial, can be served well as an alternative antiseptic agent in various fields. Typically, silver nanoparticles are smaller than 100 nm and consist of about 20–15,000 silver atoms. Due to the attractive physical and chemical properties of silver at the nanoscale, the development of silver nanoparticles is expanding in recent years and is nowadays significant for consumer and medical products.